Measuring entrepreneurship: Type, motivation, and growth - Sameeksha Desai (IZA World of Labor, 2016)
Policymakers rely on entrepreneurs to create jobs, provide incomes, innovate, pay taxes to support public revenues, create competition in industries, and much more. Due to its highly heterogeneous nature, the choice of entrepreneurship measures is critically important, impacting the diagnosis, analysis, projection, and understanding of potential and existing policy. Some key aspects to measure include the how (self-employment, new firm formation), why (necessity, opportunity), and what (growth). As such, gaining better insight into the challenges of measuring entrepreneurship is a necessary and productive investment for policymakers.
Keywords: L26; L20; O10; 330; measurement; self-employment; new firm entry density; high-growth entrepreneurship